2014
DOI: 10.1186/1746-160x-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Hearing assessment in dental practitioners and other academic professionals from an urban setting

Abstract: IntroductionExtended exposure to high-speed handpieces and other noise-intensive devices might put dentists at risk for possible hearing impairment. The aim of this study was to determine the hearing ability of dentists and other scientists for comparison.MethodsAfter approval by the ethics committee, 115 subjects (dentists and other academic professionals as controls) of both genders were enrolled in the study. Exclusion criteria were colds, ear-blockages or abnormal hearing-thresholds. An audiometric determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
2
31
0
11
Order By: Relevance
“…The results of audiometric tests showed that the hearing of dentists tended to be slightly more impaired than the hearing in the control group. For the frequencies 3 kHz and 4 kHz, those differences were statistically significant for both ears (16). In our study, hearing disorders were reported by 18.9 % of dentists, but only 5.3 % of them asked a doctor for help without any information about diagnostic procedures performed for hearing impairment diagnosis.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The results of audiometric tests showed that the hearing of dentists tended to be slightly more impaired than the hearing in the control group. For the frequencies 3 kHz and 4 kHz, those differences were statistically significant for both ears (16). In our study, hearing disorders were reported by 18.9 % of dentists, but only 5.3 % of them asked a doctor for help without any information about diagnostic procedures performed for hearing impairment diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…Rezultati audiometrijskih testova pokazali su da je sluh stomatologa nešto oštećeniji u usporedbi s kontrolnom skupinom. Na frekvencijama od 3 i 4 kHz ove razlike bile su čak i statistički značajne na oba uha (16). U ovom istraživanju o problemima sa sluhom izvijestilo je 18,9 % ispitanika, no samo njih 5,3 % tražilo je pomoć liječnika, ali nema informacija o provedenim dijagnostičkim postupcima u svrhu postavljanja dijagnoze.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Essa é outra característica da organização de trabalho desses profissionais, que geralmente trabalham em um ambiente com alta tendência a ruídos, tais como os provenientes de motor de alta rotação, compressor, sugadores de saliva, além de ar condicionadofontes emissoras que, somadas, podem levar o profissional a um comprometimento da audição e de suas atividades ocupacionais 37,38 .…”
Section: Tabela 4 Pontuação Do íNdice De Capacidade Para O Trabalho (unclassified
“…We did not measure hearing among dental professionals, as has been done in a number of previous studies (4,20). Rather, we set out to better characterize noise exposures during dental work, and to assess possible differences in exposure profiles between dentists, dental hygienists and dental students.…”
Section: Introductionmentioning
confidence: 99%